Not Only What but Also When: A Theory of Dynamic Voluntary Disclosure - Guttman, Ilan; Kremer, Ilan; Skrzypacz, Andrzej (American Economic Review, 2014)
We examine a dynamic model of voluntary disclosure of multiple pieces of private information. In our model, a manager of a firm who may learn multiple signals over time interacts with a competitive capital market and maximizes payoffs that increase in both period prices. We show (perhaps surprisingly) that in equilibrium later disclosures are interpreted more favorably even though the time the manager obtains the signals is independent of the value of the firm. We also provide sufficient conditions for the equilibrium to be in threshold strategies. (JEL D21, D82, G32, L25)